2004
DOI: 10.1897/03-26
|View full text |Cite
|
Sign up to set email alerts
|

Fish full life‐cycle testing for androgen methyltestosterone on medaka (Oryzias latipes)

Abstract: Abstract-We studied the chronic effects of methyltestosterone (MT) on reproductive status of medaka (Oryzias latipes) over two generations under continuous exposure to verify the applicability of the fish full life-cycle test (FFLC) for this androgen with this species. The exposure of parental (F0) medaka to MT was begun on embryos within 12 h postfertilization and continued for up to 101 d; assessment endpoints included embryological development, hatching, posthatch survival, growth, sexual differentiation, r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
33
0
3

Year Published

2004
2004
2019
2019

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 83 publications
(38 citation statements)
references
References 40 publications
0
33
0
3
Order By: Relevance
“…Exposures of freshwater fish to EDCs that include an entire life cycle have demonstrated increased sensitivity of subsequent generations measured by fecundity and survival of zebrafish [30], and changes of hepatic vitellogenin and incidence of testisova in medaka [11,31,32]. Multiple-generation exposures of sheepshead minnow to Tb in the present study and to 17b-estradiol [4,5] have demonstrated that in some cases, short-term adult exposures may not effectively predict the impacts on continuously exposed populations.…”
Section: Discussionmentioning
confidence: 59%
See 2 more Smart Citations
“…Exposures of freshwater fish to EDCs that include an entire life cycle have demonstrated increased sensitivity of subsequent generations measured by fecundity and survival of zebrafish [30], and changes of hepatic vitellogenin and incidence of testisova in medaka [11,31,32]. Multiple-generation exposures of sheepshead minnow to Tb in the present study and to 17b-estradiol [4,5] have demonstrated that in some cases, short-term adult exposures may not effectively predict the impacts on continuously exposed populations.…”
Section: Discussionmentioning
confidence: 59%
“…Trenbolone produced ovotestes in all female mosquitofish fry that were reared in water containing 1.0 or 10 mg/L [27]. Exposure to the androgen methyltestosterone produced a dose-related increase in similarly degenerated oocytes in medaka [28] and 3 of 20 medaka exposed to 27.75 ng/L exhibited testis-ova gonads [11]. In the present study, atypical ovaries and/or intersex occurred in the F1 generation exposed to only the 0.13 and 0.87 mg Tb/L treatments and was accompanied by significantly reduced reproduction, increased numbers of abnormal embryos and infertile eggs, and reduced hatch of offspring.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…When adult medaka exposed to 20 g/l of TCS, hatching rates of the offspring (F1) decreased significantly [12]. In addition, hatching rates and time to hatch of offspring of medaka exposure to androgen methyltestosterone was significantly less than that of the control [44].…”
Section: Hatching Rates Time To Hatching and Sex Ratio Of F1 Generationmentioning
confidence: 92%
“…number of nuptial tubercles in fathead minnow, number of papillary processes in medaka). Quantitative analysis can be performed on semi-empirical observations of secondary sex attributes in chemically exposed fish Seki et al, 2004). An excellent example is provided by Papoulias et al (2000), who used a readily available statistical software package (SPSS, Chicago IL) to perform stepwise discriminant analysis to assess the predictability of secondary sex characteristics in identifying genotypic sex in the medaka.…”
mentioning
confidence: 99%